Safety and Efficacy of MLC601 in Iranian Patients after Stroke: A Double-Blind, Placebo-Controlled Clinical Trial - A. A. Harandi; R. Abolfazli; A. Hatemian; K. Ghragozlee; M. Ghaffar-Pour; M. Karimi; S. Shahbegi; H. Pakdaman; M. Tabasi; A. L. Tabatabae; A. Nourian (Stroke Research and Treatment)
Objective. To investigate the safety and efficacy of MLC601 (NeuroAid) as a traditional Chinese medicine on motor recovery after ischemic stroke. Methods. This study was a double-blind, placebo-controlled clinical trial on 150 patients with a recent (less than 1 month) ischemic stroke. All patients were given either MLC601 (100 patients) or placebo (50 patients), 4 capsules 3 times a day, as an add-on to standard stroke treatment for 3 months. Results. Sex, age, elapsed time from stroke onset, and risk factors in the treatment group were not significantly different from placebo group at baseline (P>.05). Repeated measures analysis showed that Fugl-Meyer assessment was significantly higher in the treatment group during 12 weeks after stroke (P<.001). Good tolerability to treatment was shown, and adverse events were mild and transient. Conclusion. MLC601 showed better motor recovery than placebo and was safe on top of standard ischemic stroke medications especially in the severe and moderate cases.